PENGARUH CITRA TUJUAN WISATA DAN KEPUASAN WISATAWAN TERHADAP INTENSI BERKUNJUNG KEMBALI WISATAWAN MANCANEGARA DI DAERAH ISTIMEWA YOGYAKARTA - Nurhayati, Neneng; Sahrah, Alimatus (Kepariwisataan: Jurnal Ilmiah, 2017)
The objective of this study is to predict the effect of tourism destination image and tourist satisfaction on foreign tourists’ intention to revisit the Special Region of Yogyakarta. Subjects of the study were 90 foreign tourists of 20 to 60 years old. The data used in the study were collected using a revisiting intention scale, a tourism destination image scale, and a tourist satisfaction scale. The data were analyzed by using a multiple liniear regression technique. Results of the study show that tourism destination image and tourist satisfaction simultaneously had a significantly positive effect on the foreign tourists’ revisiting intention with p = 0,000 (p < 0,01) and a determinant coefficient of 0,189. This means that tourism destination image and tourist satisfaction were simultaneously able to predict the revisiting intention of 18,9 %, so that 81,1 % was predicted by other variables that were not examined in the study. In addition, tourism destination image partially had a significantly positive. Effect on the revisiting intention with the regression coefficient of p = 0,000 (p < 0,01) and a determinant coefficient of 0,109 or 10,9 %, while tourist satisfaction partially had a significantly positive effect on the revisiting intention with p = 0,000 (p < 0,01) and a determinant coefficient of 0,16 or 16 % on the revisiting intention. Keywords: Tourism Destination Image, Tourism Satisfaction, Revisiting Intention